OPTIMAL CONTRACTS IN A MULTI-PURPOSE TASK - Nykyforchyn, I. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
In the paper a famous multitask model of principal-agent relations is enhanced with the requirement that a reward is paid only if some minimal threshold in each type of workis attained. We deduce and analyze formulae for the expectedutility of an agent and propose a method to find his optimal behavior depending on the reward function parameters.